A Review on The Improvement of Extruded Food Processing Equipment: Extrusion Cooking in Food Processing - Abilmazhinov, Yermek; Bekeshova, Gulvira; Nesterenko, Anton; Dibrova, Zhanna; Ermolaev, Vladimir; Ponomarev, Evgeny; Vlasova, Valentina (Food Science and Technology, 2023)
The extrusion technique, which combines mixing, shaping, texturing, and heating to create a unique food product, is gaining popularity in the worldwide agro-food processing sector. Extrusion cooking is a high-temperature, short-time (HTST) method that kills bacteria and inactivates enzymes. Compared to conventional cooking, extrusion cooking is favored because of its high productivity and substantial nutrient retention. Extrusion technology has become an essential tool in the food processing industry with its various benefits over other processing methods. It is a low-cost approach that provides a platform for processing a variety of items from several food categories by altering major or minor components and processing conditions. Extrusion technique is used in the food sector to create a wide range of supplemental foods, pet foods, morning cereals, pasta, snacks, and other textured foods. It's a low-cost method of reintroducing food processing waste and by-products into the food supply. Extrusion technology's flexibility allows for the production of value-added products and nutritionally dense fortified goods using various low-cost raw ingredients. Extruded goods are microbiologically safe, have a longer shelf life, and have less moisture content. This technology's advantages include product diversity and excellent quality and new food productivity and low processing time.